Protecting Users from Malicious Mobile Apps: A Comprehensive Security Guide for Common Users - Sachin Kediyal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article addresses the critical issue of malicious mobile native applications and their impact on user security. The article explores the evolving landscape of mobile threats, examining various categories of malicious apps and their sophisticated attack mechanisms. It analyzes threat impacts across multiple dimensions, including personal data theft, financial losses, privacy violations, and device performance degradation. The article presents a multi-layered approach to user protection, encompassing pre-installation verification, installation safety measures, and post-installation monitoring strategies. The article evaluates the effectiveness of platform-specific security tools and best practices for ongoing protection, comparing security measures across Android and iOS ecosystems. By analyzing current trends and protection mechanisms, this paper offers valuable insights for common users to enhance their mobile security posture and minimize the risk of compromise from malicious applications. The findings demonstrate the importance of implementing comprehensive security measures and maintaining vigilant security practices in the mobile computing native environment.
Keywords: Mobile Security; Malicious Applications; Threat Detection; User Protection Strategies; Security Best Practices